2023
DOI: 10.1126/scisignal.abq3362
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylated IL-33 in the nucleus stabilizes the transcription factor IRF1 in hepatocellular carcinoma cells to promote immune escape

Abstract: Interleukin-33 (IL-33) functions both as a secreted cytokine and as a nuclear factor, with pleiotropic roles in cancer and immunity. Here, we explored its role in hepatocellular carcinoma (HCC) and identified that a posttranslational modification altered its nuclear activity and promoted immune escape for HCC. IL-33 abundance was overall decreased but more frequently localized to the nucleus in patient HCC tissues than in normal liver tissues. In human and mouse HCC cells in culture and in vivo, IL-33 overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Importantly, these findings have opened up exciting possibilities for the development of novel therapeutic strategies that target the nIL-33 pathway for the treatment of various diseases. In our previous study (Wang et al 2023b), we found that SUMOylated nIL-33 promotes PDL1 expression in liver cancer cells. Thus, targeting nIL-33 with SUMOylation may serve as a therapeutic strategy.…”
Section: Role Of Nil-33 In Transcription Regulationmentioning
confidence: 81%
See 2 more Smart Citations
“…Importantly, these findings have opened up exciting possibilities for the development of novel therapeutic strategies that target the nIL-33 pathway for the treatment of various diseases. In our previous study (Wang et al 2023b), we found that SUMOylated nIL-33 promotes PDL1 expression in liver cancer cells. Thus, targeting nIL-33 with SUMOylation may serve as a therapeutic strategy.…”
Section: Role Of Nil-33 In Transcription Regulationmentioning
confidence: 81%
“…Thus, we referred to this technology (Henning et al 2022) and attempted to construct a SENP2-targeting nIL-33 chimera (STACs) targeting SUMO enzymes. In short, using SUMO specific protease 2 (SENP2) as a recruiter to recruit nIL-33 from SUMOylation, thereby removing SUMO molecules that bind to nIL-33, stabilizing four potential sites for SUMOylation identified within the protein (Wang et al 2023b). These modifications have been shown to modulate the function of IL-33, with SUMOylation enhancing its activity in promoting the proliferation of T cells.…”
Section: Role Of Nil-33 In Transcription Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concretely, in HCC, SUMO1-mediated SUMOylation via the IKII 265-268 SIM site of pyruvate kinase M2 (PKM2) relocates PKM2 from the cytoplasm to the nucleus, leading to glycolytic reprogramming and cancer progression via EMT induction and signal transducer and activator of the transcription 3 (STAT3) signaling pathway 26 . Likewise, Ran-binding protein 2 (RanBP2)-mediated SUMOylation of interleukin-33 (IL-33) at K54 facilitates its nuclear shuttling, therefore resulting in immune evasion in HCC 27 . Furthermore, in prostate cancer, SUMOylation of tumor suppressor gene p53, which is mediated by the RanBP2/SUMO1/Ubc9 complex, facilitates its translocation from the nucleus to the cytoplasm, promoting malignancy progression 28 .…”
Section: Sumoylation Cascade and Biological Significance In Tumorsmentioning
confidence: 99%
“…Specifically, SUMOylation of programmed cell death protein-1 ligand (PD-L1) by TRIM28, an E3 ubiquitin ligase and E3 SUMO ligase, stabilizes PD-L1 via hampering PD-L1 ubiquitination and enhancing PD-L1 SUMOylation, leading to the T cell inactivation and immune evasion in gastric cancer 74 . Additionally, E3 ligase RanBP2-induced SUMOylation of nuclear factor IL-33 at K54 prevents the degradation of transcription factor IRF1 which elevates the expression of PD-L1, a T cell immune checkpoint ligand, in HCC cells, ultimately leading to the inactivation of T cells and immune surveillance 27 .…”
Section: The Role Of Sumoylation In Sustaining Malignancymentioning
confidence: 99%